CO2 bubble-regulated porous architecture of CS@ZIF-8 microspheres for enhanced alcalase immobilization with improved walnut protein hydrolysis - Jiangjuan Yuan; Xueying Liu; Mingyao Li; Feng Jin; Baokai Cui; Jingzhen Chen; Changzhu Li; Fengjun Wang (Carbohydrate Polymers, 2026)

From structural remodeling to cytoprotection: pH-regulated assembly of walnut protein hydrolysate fibril-chlorogenic acid complexes and transcriptomic insights - Chang Li; Jiangjuan Yuan; Junyang Long; Feng Jin; Baokai Cui; Jingzhen Chen; Changzhu Li; Fengjun Wang (Food Bioscience, 2026)

Corrigendum to ’Visible light photocatalytic enhanced heterogeneous cobalt catalyzed peroxymonosulfate synergistic process to degradation atrazine: Efficiency, influencing factors, by-products removal and mechanism’[Volume 159, January 2026, Pages 166-177] - Qingkong Chen; Jieyu Xia; Fengjun Liu; Jianping Fan; Peng Yan; Mika Sillanpää (Journal of Environmental Sciences, 2026)

Methacryloxyethyl sulfobetaine (SBMA) based hydrogel with functional enhancement by acrylamide, glycerol, and thymol for strawberry preservation - Zhichao Yang; Xiaohong Guo; Ziqiang Qin; Fengjun Guo; Di Wu; Bangdi Liu; Kunsong Chen (Food Chemistry, 2026)

The Effect of Humic Acid From Different Raw Materials on Soil Physical and Chemical Properties and Tomato Seedling Growth - Lanjing Long; Liqin Zhao; Xiangjun Chen; Zhicheng Liu; Xue Chen; Bowen Fan; Fengjun Yang (Journal of Soil Science and Plant Nutrition, 2026)

Developing process descriptor for biological nitrogen removal in wastewater treatment - Fengjun Yin; Hao Tan; Jinjin Zheng; Zhaoming Chen; Guangyao Zhao; Di Wu; Hong Liu (Water Research, 2026)

Biodegradable polybutylene adipate terephthalate packaging with dual-functionality: Synergistic effects of curcumin coating and laser micro-perforation on sweet cherry preservation - Zhijie Zuo; Xiao Chen; Ming Li; Xinhua Zhang; Binshan Mu; Yijing Li; Zhanjun Guo; Changfeng Zhang; Xinguang Fan; Fujun Li; Fengjun Guo (Food Packaging and Shelf Life, 2026)

Flocoumafen exposure induces skeletal developmental toxicity and neurotoxicity in zebrafish (Danio rerio) - Tianyi Chen; Fengjun Fan; An Cheng; Yumei Xia; Haoze Chen; Jiakai Fang; Yangyu Chen; Tianjia Li; Anli Wang; Binjie Wang; Weixuan Yao; Yuanzhao Wu (Toxicology Letters, 2026)

Amplified radiative effects of coated black carbon aerosols over the Tibetan Plateau - Jie Sun; Gang Zhao; Jinyuan Yu; Weili Lin; Yi Chen; Chunxiang Ye; Wenxu Fang; Wenhao Zhou; Baifeng Zhu; Jiawei Yang; Zhijun Wu; Tong Liu; et al. (Atmospheric Research, 2026)

Visible light photocatalytic enhanced heterogeneous cobalt catalyzed peroxymonosulfate synergistic process to degradation atrazine: Efficiency, influencing factors, by-products removal and mechanism - Qingkong Chen; Jieyu Xia; Fengjun Liu; Jianping Fan; Peng Yan; Mika Sillanpää (Journal of Environmental Sciences, 2026)

Responses of ground and adjacent shallow foundation buildings to twin large-diameter shield tunnelling in soft clay: Case study - Cheng Kang; Rongzhu Liang; Wenxian Zhao; Wenbing Wu; Chin Jian Leo; Fengjun Chen; Dong Huang (Tunnelling and Underground Space Technology, 2025)

Functional characterization of two CCL20 chemokines in black rockfish (Sebastes schlegelii): dual roles in immune cell recruitment and direct antimicrobial defense - Fengjun Lin; Yiying Liu; Chonghui Chen; Xiaoxu Zhang; Pei Zhang; Huijun Huo; Chao Li; Qiang Fu (Fish & Shellfish Immunology, 2025)

Continuous flow synthesis of mononitrotoluene with high selectivity using acetyl nitrate in the microreactor - Rao Chen; Yuyang Xu; Mei Han; Yingjiang Lian; Fengjun Jiao; Chaoqun Yao; Guangwen Chen (Chemical Engineering Journal, 2025)

Responsive packaging that adapted to and regulated physiological metabolic of fruits and vegetables: Mechanism, application and prospects - Chunjun Chen; Yibing Ding; Yucong Feng; Xiulian Li; Chanchan Sun; Fengjun Guo; Xiangquan Zeng; Hansheng Gong; Xinguang Fan (Trends in Food Science & Technology, 2025)

A WRKY transcriptional factor, BrWRKY70, involves in stem lignification in postharvest Chinese flowering cabbage by regulating lignin synthesis - Fengjun Li; Ling Wang; Meiting Wu; Yulong Chen; Lilang Li; Hai Liu (Postharvest Biology and Technology, 2025)

The role of hydrolysis on the fibrillization of walnut protein: Self-assembly behavior, structural characteristics - Chang Li; Rui Chen; Jiangjuan Yuan; Feng Jin; Fengjun Wang (Food Chemistry, 2025)

Dietary fat powder replacement of soybean oil modulates muscle fatty acids, liver morphology and oxidation, and intestinal lipid metabolism-related gene expression in juvenile largemouth bass (Micropterus salmoides) - Lina Bai; Lei Zhang; Chen Chen; Jilin Xu; Fengjun Xie; Kai Liao (Animal Feed Science and Technology, 2025)

Transglutaminase-enhanced walnut protein isolate gels: Synergistic effects of double modification on gelation and riboflavin encapsulation - Mengxin Wang; Rui Chen; Long Wu; Feng Jin; Fengjun Wang (Food Chemistry, 2025)

Electrochemical nitrite sensing using mass transfer signal with a catalyst-free small-sized rotating disk electrode for wastewater monitoring - Fengjun Yin; Xiaohui Yang; Shun Lu; Hanlin Zhang; Ying Zhao; Sha Wang; Cheng Song; Yongzhi Li; Zhaoming Chen; Hong Liu (Water Research, 2025)

Effects of Environmentally Friendly Aquaculture Chamber Coatings on Enzyme Activities, Histology, and Transcriptome in the Liver of Larimichthys crocea - Xuan Xu; Huayu Song; Huicai Wu; Lu Zhang; Fengjun Lin; Chonghui Chen; Xiaoxu Zhang; Yiying Liu; Chao Li; Qiang Fu (Marine Biotechnology, 2025)

Near-freezing temperature alters ROS metabolism and gene transcription to enhance peach chilling tolerance and aroma quality - Hongru Liu; Hui He; Qiankun Wang; Shaozhen Li; Fengjun Guo; Changfeng Zhang; Ke Wang; Chenxia Liu; Chunfang Wang; Xiao Wang; Bingjie Chen; Yi Zhang; et al. (Food Research International, 2025)

The source-specific health risk and biological effect assessment of PAHs in Mactra veneriformis from the Bohai Sea and Yellow Sea - Zeyuan Li; Ruicheng Qi; Jingjing Miao; Yufen Li; Qiaoqiao Wang; Fengjun Lei; Manni Wu; Yuanjing Chen; Luqing Pan (Environmental Pollution, 2025)

Digital twin comprehensive models: a study of ancient tree ecological environment quality assessment based on a cyber-physical system - Yansheng Chen; Huazhi Huang; Jie Li; Zejiong Zheng; Fengjun Gao; Xiaoge Han; Yanglin Gao (Environmental Monitoring and Assessment, 2025)

A structural equation model for assessing toxic effects of polycyclic aromatic hydrocarbons on scallop Chlamys farreri and the establishment of a novel integrated biomarker index - Zeyuan Li; Ruicheng Qi; Jingjing Miao; Yufen Li; Qiaoqiao Wang; Fengjun Lei; Manni Wu; Yuanjing Chen; Luqing Pan (Marine Environmental Research, 2025)

L-glutamic acid-functionalized graphene oxide with characteristic of anti-stacking towards efficient adsorption-reduction removal of Cr(VI) - Yuxin Wang; Yueqi Chen; Fengjun Shan; Tingting Zhang; Zhenbin Zhang; Meijun Liu (Journal of Environmental Chemical Engineering, 2024)

Detection of Camellia oleifera fruit maturity in orchards based on modified lightweight YOLO - Xueyan Zhu; Fengjun Chen; Yili Zheng; Chuang Chen; Xiaodan Peng (Computers and Electronics in Agriculture, 2024)

Liquid-liquid addition reaction of ethylene oxide with hydrazine hydrate in microreactors: Kinetics and process optimization - Haiyun Ma; Lixia Yang; Chaoqun Yao; Shuainan Zhao; Fengjun Jiao; Guangsheng Luo; Guangwen Chen (Chemical Engineering Journal, 2024)

Megaripple stripes in the Qaidam Basin, China: Morphology, grain size and sedimentary characteristics - Lijie Wang; Fengjun Xiao; Zhibao Dong; Huirong Ma; Hao Chen (Geomorphology, 2024)

Core microbes identification and synthetic microbiota construction for the production of Xiaoqu light-aroma Baijiu - Huan Wang; Yumei Wang; Yulei Ruan; Dan Ma; Han Wang; Shengzhi Yang; Linjie Lyu; Fengjun Yang; Xiaole Wu; Yefu Chen (Food Research International, 2024)

Enhanced separation performance of composite nanofiltration membranes via electrostatic air spray PSS/PEI interlayer - Tixi He; Fengjun Chen (Desalination, 2024)

Evaluation of toxicity of heated tobacco products aerosol and cigarette smoke to BEAS-2B cells based on 3D biomimetic chip model - Hongjuan Wang; Fengjun Lu; Yushan Tian; Sen Zhang; Shulei Han; Yaning Fu; Jun Li; Pengxia Feng; Zhihao Shi; Huan Chen; Hongwei Hou (Toxicology in Vitro, 2024)

A comprehensive assessment framework for the risk and source of polycyclic aromatic hydrocarbons (PAHs) using two weight of evidence (WOE) approaches in bays of Shandong Province, China - Zeyuan Li; Ruicheng Qi; Jingjing Miao; Yufen Li; Qiaoqiao Wang; Fengjun Lei; Manni Wu; Yuanjing Chen; Luqing Pan (Journal of Cleaner Production, 2023)

Crustal structure beneath the northern part of the southeastern Tibetan Plateau revealed by a seismic dense nodal array - Shunjia Tan; Xiaobo Tian; Xiangzhi Zeng; Fengjun Nie; Chen Qu; Changqing Yu (Journal of Asian Earth Sciences, 2023)

Rice bran is a key structure affecting high nutrition and low toxicity of indica hybrid rice (Oryza sativa L.) - Yu Fan; Yujie Yuan; Zhiyou Gong; Yajun Wang; Xiufeng Mei; Fengjun Yan; Tao Wang; Fei Deng; Yong Chen; Xiaolong Lei; Jianfeng Hu; Youfeng Tao; et al. (Journal of Cereal Science, 2023)

Sustainability assessment of a conceptual multipurpose offshore platform in the South China Sea - Shanyu Chen; Fengjun Duan; Shigeru Tabeta (Environment, Development and Sustainability, 2023)
An offshore multipurpose floating platform (MPFP) combines different marine technologies to serve industry needs using one infrastructure; the aim of an MPFP is enlarging the synthesis benefits and reducing the negative impacts. Ocean thermal energy conversion (OTEC) in particular has attracted significant attention for its great potential and low environmental risk. This research demonstrates the system design of a conceptual MPFP in the South China Sea, evaluating its economic and environmental sustainability using an inclusive index. The system is based on a modular floating structure with a designed lifetime of 50 years. Tuna aquaculture, microalgae cultivation and processing, and the OTEC energy infrastructure are integrated to increase the profitability of the applications. We adopted a high-yield photobioreactor microalgae cultivation system and a low-cost barge-type floating structure combined with a semisubmergible to reduce the required area and cost of the floating structure and improve the sustainability of the system. The inclusive impact index “Triple-I-light ( III light )” was calculated to evaluate the environmental sustainability and economic feasibility of the floating system. The result shows that the new system becomes environmentally neutral (EF = BC) at a lifetime of 11.5 years, showing sustainability ( III light ≤ 0) at a lifetime of 20 years. The proposed system can produce fish with no external energy or feed supply. An autonomous system, such as the one proposed here, is considered very effective when it comes to utilizing the ocean and contributing to a sustainable society.

Ceramsite made from remediated soil: A risk assessment of its potential role serving as urban street cushion - Chi Zhang; Genfu Wang; Fengjun Xu; Zhenghua Wu; Chaofeng Shen; Chao Wu; Zhong Zhong; Jianmeng Chen (Bulletin of Environmental Contamination and Toxicology, 2023)

Promotion and inhibition effects of wax on methane hydrate formation and dissociation in water-in-oil emulsions - Shikun Tong; Pengfei Li; Fengjun Lv; Zhiyuan Wang; Weiqi Fu; Jianbo Zhang; Litao Chen; Xuerui Wang (Fuel, 2023)

Synergistic and antagonistic effects of preharvest salicylic acid and postharvest 1-methylcyclopropene treatments on the storage quality of apricot - Changchang Liang; Xinzhi Cui; Chanchan Sun; Sunxiang Ye; Ningxin Huang; Rong Chen; Aidi Zhang; Yanqing Yang; Hansheng Gong; Shuyang Sun; Fengjun Guo; Xinguang Fan; et al. (Food Chemistry, 2023)

Accumulated temperature and allocation of photo-thermal resources are key meteorological factors affecting rice cadmium content - Wei Zhou; Fengjun Yan; Yu Fan; Chi Zhang; Fan Yang; Qi Liu; Tao Wang; Bo Li; Yong Chen; Fei Deng; Jianfeng Hu; Xiaolong Lei; et al. (European Journal of Agronomy, 2023)

The amendment of Organic matters enhances the anaerobic dechlorination of Polychlorinated Biphenyls in Paddy Soil - Jingwen Chen; Fengjun Xu; Kai Yang; Chen Chen; Jixing Wan; Chaofeng Shen (Bulletin of Environmental Contamination and Toxicology, 2022)

Differences in Rice Productivity and Growth Attributes Under Different Paddy-Upland Cropping Systems - Wei Zhou; Tao Wang; Yong Fu; Zhiping Yang; Qi Liu; Fengjun Yan; Yong Chen; Youfeng Tao; Wanjun Ren (International Journal of Plant Production, 2022)

Removal of Hg2+ from desulfurization wastewater by tannin-immobilized graphene oxide - Heng Chen; Fengjun Liu; Chenjian Cai; Hao Wu; Linjun Yang (Environmental Science and Pollution Research, 2022)

Development characteristics and construction prospects for a multi-integrated economic zone in the South China Sea Region - Fengjun Jin; Zuolin Yao; Zhuo Chen (Journal of Geographical Sciences, 2021)

Residual nitrogen from preceding garlic crops is important for double-cropped rice - Wei Zhou; Tao Wang; Yong Fu; Zhiping Yang; Qi Liu; Fengjun Yan; Yong Chen; Youfeng Tao; Nkrumah Malik; Wanjun Ren (Nutrient Cycling in Agroecosystems, 2020)

Evolution of transportation in China since reform and opening up: Patterns and principles - Fengjun Jin; Zhuo Chen (Journal of Geographical Sciences, 2019)

Complete mitochondrial genome of the Himalayan Musk Deer, Moschus leucogaster, with phylogenetic implication - Keji Guo; Fengjun Li; Qi Zhang; Shunde Chen (Conservation Genetics Resources, 2019)

An automatic multi-class coronary atherosclerosis plaque detection and classification framework - Fengjun Zhao; Bin Wu; Fei Chen; Xin Cao; Huangjian Yi; Yuqing Hou; Xiaowei He; Jimin Liang (Medical & Biological Engineering & Computing, 2019)

Complete mitochondrial genome of the Himalayan Monal Lophophorus impejanus (Phasianidae), with phylogenetic implication - Yang Chen; Fengjun Li; Qi Zhang; Qiong Wang (Conservation Genetics Resources, 2018)

Development history and accessibility evolution of land transportation network in Beijing-Tianjin-Hebei region over the past century - Yu Chen; Fengjun Jin; Yuqi Lu; Zhuo Chen; Yu Yang (Journal of Geographical Sciences, 2018)

Novel deletion of SLC34A2 in Chinese patients of PAM shares mutation hot spot with fusion gene SLC34A2–ROS1 in lung cancer - Shang Dandan; Chen Yuqin; Lu Wei; Peng Ziheng; Zhou Dapeng; Yang Jianzhu; Xin Xin; Liu Yonghong; Tian Fengjun (Journal of Genetics, 2018)

Complete mitochondrial genome of the Burmese Short-Tailed Shrew, Blarinella wardi (Mammalia, Soricidae) - Fengjun Li; Xuming Wang; Qi Zhang; Haijun Jiang; Haixue Wei; Qing Wang; Shunde Chen; Shaoying Liu (Conservation Genetics Resources, 2018)

The complete mitochondrial genome of Chinese Shrew, Sorex sinalis (Soricidae) - Xuming Wang; Fengjun Li; Qi Zhang; Haijun Jiang; Shunde Chen; Shaoying Liu (Conservation Genetics Resources, 2018)

A monocentric centerline extraction method for ring-like blood vessels - Fengjun Zhao; Feifei Sun; Yuqing Hou; Yanrong Chen; Dongmei Chen; Xin Cao; Huangjian Yi; Bin Wang; Xiaowei He; Jimin Liang (Medical & Biological Engineering & Computing, 2018)

Location characteristics and differentiation mechanism of logistics nodes and logistics enterprises based on points of interest (POI): A case study of Beijing - Guoqi Li; Fengjun Jin; Yu Chen; Jinjuan Jiao; Sijing Liu (Journal of Geographical Sciences, 2017)

Late Palaeozoic tectonic setting of the southern Alxa Block, NW China: constrained by age and composition of diabase - Yiping Zhang; Jin Zhang; Xuanhua Chen; Yannan Wang; Heng Zhao; Fengjun Nie; Beihang Zhang (International Geology Review, 2017)

A highly robust and optimized sequence-based approach for genetic polymorphism discovery and genotyping in large plant populations - Ning Jiang; Fengjun Zhang; Jinhua Wu; Yue Chen; Xiaohua Hu; Ou Fang; Lindsey J. Leach; Di Wang; Zewei Luo (Theoretical and Applied Genetics, 2016)

Quantitative analysis of vascular parameters for micro-CT imaging of vascular networks with multi-resolution - Fengjun Zhao; Jimin Liang; Xueli Chen; Junting Liu; Dongmei Chen; Xiang Yang; Jie Tian (Medical & Biological Engineering & Computing, 2016)

Molecular characterization and expression analyses of ST8Sia II and IV in piglets during postnatal development: lack of correlation between transcription and posttranslational levels - Xi Zhu; Yue Chen; Nai Zhang; Zhiqiang Zheng; Fengjun Zhao; Ni Liu; Chunlong Lv; Frederic A. Troy; Bing Wang (Glycoconjugate Journal, 2015)